2020
DOI: 10.1093/cid/ciaa1770
|View full text |Cite
|
Sign up to set email alerts
|

Population Impact of Girls-Only Human Papillomavirus 16/18 Vaccination in The Netherlands: Cross-Protective and Second-Order Herd Effects

Abstract: Background Human papillomavirus (HPV) vaccination programs achieve substantial population-level impact, with effects extending beyond protection of vaccinated individuals. We assessed trends in HPV prevalence up to eight years post-vaccination among men and women in the Netherlands, where bivalent HPV (2vHPV) vaccination, targeting HPV16/18, has been offered to (pre)adolescent girls since 2009 with moderate vaccination coverage. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…This result is in line with the conclusions of Lehtinen et al [23]. A recent study carried out in the Netherlands, a country with relatively moderate girls-only bivalent vaccine uptake, has also shown a herd effect between heterosexual men and unvaccinated women since the vaccination program began [24].…”
Section: Discussionsupporting
confidence: 90%
“…This result is in line with the conclusions of Lehtinen et al [23]. A recent study carried out in the Netherlands, a country with relatively moderate girls-only bivalent vaccine uptake, has also shown a herd effect between heterosexual men and unvaccinated women since the vaccination program began [24].…”
Section: Discussionsupporting
confidence: 90%
“…In our age group 20–23 years old, there was an increase of HPV types 53, 58 and 67 over time. This so-called type-replacement is already found in other population-based trials with an increase of HPV types 39 and 51 in the Scandinavian and an increase of HPV types 54 and 56 in the Dutch populations (Gray et al , 2018; Hoes et al , 2021). Earlier, in 2016, an increase of types 39, 52, 53, 58 and 73 was observed in a meta-analysis (Mesher et al , 2016).…”
Section: Discussionsupporting
confidence: 66%
“…Even the most recent studies, despite longer times since vaccine introduction (up to 8-10 years), had sample sizes too small to detect significant NV-prevalence variation, if it exists. [21,32,33] It seems important to note here that several studies reported a rapid reduction in the prevalences of HPV-31, -33 and -45 after vaccine introduction. [21,22,24,29] Nevertheless, this rapid reduction which differs from that observed in our simulations is most likely a direct protective effect of the vaccine via cross-reactivity, i.e., vaccine-induced antibodies able to neutralize these NV genotypes [18,27,28,34] but phylogenetically related to V genotypes.…”
Section: Discussionmentioning
confidence: 82%
“…Compared to our model simulations, most studies had smaller sample sizes than the required number of subjects we estimated and they were conducted only a few years after vaccine introduction. Even the most recent studies, despite longer times since vaccine introduction (up to 8–10 years), had sample sizes too small to detect significant NV-prevalence variation, if it exists [ 21 , 32 , 33 ]. It seems important to note here that several studies reported a rapid reduction in the prevalences of HPV-31, -33 and -45 after vaccine introduction [ 21 , 22 , 24 , 29 ].…”
Section: Discussionmentioning
confidence: 99%